Structural dissection of human translation elongation factor 1Bγ (eEF1Bγ): expression of full-length protein and its truncated forms - Trosiuk, T.V.; Liudkovska, V.V.; Shalak, V.F.; Negrutskii, B.S.; El’skaya, A.V. (Вiopolymers and Cell, 2014)
Aim. To gain more insights into properties of the human translation elongation factor eEF1Bγ and its interaction with partners we intended to produce the full-length protein and its truncated forms. Methods. cDNAs encoding truncated forms of eEF1Bγ were generated by PCR amplification with respective primers and cloned into vectors providing polyhistidine, glutathione S-transferase or maltose binding protein tags. The recombinant proteins were expressed in Escherichia coli and purified by affinity chromatography. An aggregation state of the proteins was analyzed by analytical gel filtration. Results. The expression, purification and storage conditions for the full-length recombinant His-eEF1Bγ were optimized. Several truncated forms of eEF1Bγ were also expressed and purified to homogeneity. Two short variants of C-terminal domain comprising amino acids 263–437 or 228–437 were obtained in monomeric state. Two short variants of N-terminal domain comprising amino acids 1–33 or 1–230, fused with glutathione S-transferase, were obtained and estimated to be dimers by gel filtration. The mutants of N-terminal domain comprising amino acids 1–93 or 1–165, fused with maltose binding protein, were obtained as soluble high molecular weight aggregates only. Conclusions. The purified recombinant His-eEF1Bγ and several truncated forms of the protein were obtained and characterized. These protein variants will be used for further studies on the protein-protein interaction. Мета. Для детального вивчення властивостей фактора елонгації трансляції eEF1Bγ людини і його взаємодії з партнерами оптимізувати експресію кДНК повнорозмірного білка та його вкорочених форм. Методи. кДНК, які кодують вкорочені форми eEF1Bγ, синтезували методом ПЛР-ампліфікації з відповідними праймерами і клонували у вектори, що містять які афінну мітку полігістидинову послідовність, глутатіон S-трансферазу або білок, який зв’язує мальтозу. Рекомбінантні білки експресували в бактеріях і очищували афінною хроматографією. Агрегатний стан отриманих білків аналізували з використанням аналітичної гель-фільтрації. Результати. Оптимізовано експресію, очищення та умови зберігання повнорозмірного рекомбінантного His-eEF1Bγ. Також експресовано і очищено до гомогенного стану кілька вкорочених форм eEF1Bγ. Дві вкорочені форми С-кінцевого домену, які містять амінокислотні залишки 263–437 і 228–437, отримано у вигляді розчинних мономерних білків. Дві вкорочені форми N-кінцевого домену, що містять амінокислотні залишки 1–33 і 1–230, злиті з глутатіон S-трансферазою, одержано у вигляді димерів згідно з результатами гель-фільтрації. Інші делеційні мутанти, які містять амінокислотні залишки 1–93 і 1–165 N-кінцевого домену та злиті з білком, що зв’язує мальтозу, можуть бути отримані лише у вигляді розчинних високомолекулярних агрегатів. Висновки. Отримано і охарактеризовано рекомбінантний білок His-eEF1Bγ та його чотири вкорочені форми. Ці форми в подальшому буде використано для вивчення білково-білкових взаємодій. Цель. Для более детального изучения свойств человеческого фактора элонгации трансляции eEF1Bγ и его взаимодействия с партнерами оптимизировать експрессию кДНК полноразмерного белка, а также его усеченных форм. Методы. кДНК, кодирующие укороченные формы eEF1Bγ, генерировали методом ПЦР-амплификации с соответствующими праймерами и клонировали в векторы, содержащие в качестве аффинной метки полигистидиновую последовательность, глутатион S-трансферазу или белок, связывающий мальтозу. Рекомбинантные белки экспрессировали в бактериях и очищали аффинной хроматографией. Агрегатное состояние полученных белков анализировали с помощью аналитической гель-фильтрации. Результаты. Оптимизированы экспрессия, очистка и условия хранения полноразмерного рекомби- нантного His-eEF1Bγ. Также експрессированы и очищены до гомогенного состояния несколько усеченных форм eEF1Bγ. Две укороченные формы С-концевого домена, содержащие аминокис- лотные остатки 263–437 и 228–437, получены в виде растворимых мономерных белков. Две укороченные формы N-концевого домена, содержащие аминокислотные остатки 1–33 и 1–230, слитые с глутатион S-трансферазой, получены в виде димеров по результатам гель-фильтрации. Другие делеционные мутанты, содержащие аминокислотные остатки 1–93 и 1–165 N-концевого домена и слиты с белком, связывающим мальтозу, могут быть получены только в виде растворимых высокомолекулярных агрегатов. Выводы. Получены и охарактеризованы рекомбинантный фактор элонгации трансляции His-eEF1B и его четыре усеченные формы, которые в дальнейшем будут использованы для изу- чения белково-белковых взаимодействий.